Effect of consecutive steeping on antioxidant potential of green, oolong and black tea. (11th September 2017) - Islam, Shaikh N.; Farooq, Sumaya; Sehgal, Amit
Summary: After water, tea is considered to be one of the most consumed drinks worldwide. To get the maximum benefit from the whole‐leaf teas, the manufacturers provide instruction that these teas can be steeped 2–3 times over 6–8 h. In this study, the effect of consecutive steeping on radical‐scavenging ability of whole leaf green tea (unfermented), oolong tea (partially fermented) and black tea (fully fermented) was determined. Green tea showed the highest level of antioxidant activity, total phenolic and flavonoid content followed by oolong tea and black tea irrespective of the number of steeping done. The result also demonstrated that re‐steeping reduced the antioxidant potential of teas. Moreover, it was revealed that green tea is the best candidate for re‐steeping followed by oolong and then black tea. Abstract : Among the studied whole leaf teas, green tea is the best candidate for re‐steeping followed by oolong and then black tea. Don't use the previous graphical abstract. I am sending better quality image of graphical abstract as an attachment.